Frequency regulation of a maiden structured power system with integrated renewable energy source by a fuzzy - tuned fractional order controller. Issue 3 (14th September 2022) - Nayak, Anurekha; Maharana, Manoj Kumar; Sidhu, Tarlochan; Padmanaban, Sanjeevikumar; Panda, Gayadhar
ABSTRACT: In this paper, a hybrid fuzzy cascaded fractional order proportional integral-fractional order proportional derivative (FCFOPI-FOPD) controller improves the frequency regulation of a renewable energy source (RES) integrated power system. The frequency response characteristics of a two-area non-linear thermal-hydro-wind model under various operating situations are explored with an emphasis on the extensive usage of renewable energy sources (RES) in modern power systems. The power system in this study is developed using an innovative combination of a standard dynamic model of the steam turbine and the actual physical position of the generation rate constraint in the power plant model. The suggested FCFOPI-FOPD hybrid controller minimizes a power system's frequency deviation caused by specific differences in the pre-scheduled load. The effectiveness of a proposed FCFOPI-FOPD hybrid controller in alleviating system frequency variations under various perturbations was determined using MATLAB Simulink analysis. Comprehensive results show that the FCFOPI-FOPD hybrid controller outperforms the fuzzy-structured fractional order proportional integral and derivative (FOPID) and the proportional and integral controllers. The results also demonstrate that the proposed controller improves the settling time of frequency variations in area-1, area-2, and tie-line power deviation by 47%, 51%, and 66% compared to the responses obtained with the fuzzy FOPID controller.